2016
DOI: 10.1039/c5ra14946k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion as a topical delivery system of antipsoriatic drugs

Abstract: Nanoemulsion as a potential enhancer for the treatment of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 152 publications
0
33
0
Order By: Relevance
“…MASOUMI 1 , M. BASRI 1 , S.S. DA COSTA 1 and N. AHMAD 2 methods: either using high-energy or low-energy emulsification methods (both covering the particle size ranging less than 500 nm) [7,8]. High energy emulsification methods include high pressure homogeniser, microfluidization and ultrasonication, while the low energy emulsification method include phase inversion composition (PIC), phase inversion temperature (PIT) and dilution of microemulsion [9].…”
Section: Optimization Of Hydrocortisone-loaded Nanoemulsion Formulatimentioning
confidence: 99%
“…MASOUMI 1 , M. BASRI 1 , S.S. DA COSTA 1 and N. AHMAD 2 methods: either using high-energy or low-energy emulsification methods (both covering the particle size ranging less than 500 nm) [7,8]. High energy emulsification methods include high pressure homogeniser, microfluidization and ultrasonication, while the low energy emulsification method include phase inversion composition (PIC), phase inversion temperature (PIT) and dilution of microemulsion [9].…”
Section: Optimization Of Hydrocortisone-loaded Nanoemulsion Formulatimentioning
confidence: 99%
“…17 Though many options are offered by topical treatment, such complications as staining, bad odor, side effects, and difficulty in application have limited their usage. 15, 18 Malik et al has reported hijama as a traditional topical treatment for treating psoriasis. However, this treatment is not very practical, since it needs to be performed in aseptic conditions by a well-trained hijama physician.…”
Section: Introductionmentioning
confidence: 99%
“…Isotropic, transparent, kinetically stable; high solubilization capacity for both lipophilic & hydrophilic drugs [6] Careful selection of formulation components essential to avoid skin irritation Vesicular carriers Solid Lipid nanoparticles Solid lipid nanoparticles reported to deform in shape and melt after application to skin reducing the skin barrier and causing occlusion on the skin surface favoring the penetration of the active [7,8].…”
Section: Stability Influenced By Factors Such As Ph and Temperature Chamentioning
confidence: 99%